Subsidies Law and Adjustment Policies: The 1982 EEC-US Steel Dispute Revisited - Zimbler, Brian L. (Tufts Archival Research Center, 2005)
Volume 8, Issue 2. Summer In recent years most of the developed nations have shared problems of competitiveness and obsolescence in the manufacturing sectors of their economies, especially in the steel industries. Proposals for domestic adjustment policies, including government intervention to revitalize these industries, have prompted increased attention in some countries and implementation in others. Brian Zimbler explores the ramifications of such government intervention to support industrial competitiveness by examining the relationship between adjustment policies and the traditional agreements and rules which govern international trade. Finding that present rules are ill-suited for coping with widespread use of adjustment policies, Zimbler suggests - reasoning from the U.S. and international legal experience with the 1982 EEC-US steel dispute - that the developed countries should develop a cooperative and complementary set of adjustment policies through international negotiation in order to concentrate on sharing gains rather than apportioning losses.